La palabra incómoda: narrativas sobre la experiencia de vida de Selena, Juana y Camila, tres mujeres excombatientes de las Autodefensas Unidas de Colombia (2020)
La palabra incómoda is a research-creation project about life experiences narratives by Camila, Juana and Selena, three women ex-combatants from the AUC. This research was designed from two components: one theoretical and the other practical. In the theoretical component, we proposed to contribute to the reflection about truth discursive regimes, through which the memories of the life experiences of AUC ex-combatants have been produced, enunciated, constructed and, mainly, validated in Colombia. In the practical component, we proposed the design and development an alternative methodology to the institutionalized: an experiences laboratory for the construction and production of silenced memories about the life experience and the war experience told by three women ex-combatants from the AUC. In this research we are interested in life experiences narratives, which are uncomfortable because they do not belong to the truth legitimizing frameworks (Letered and Legal).